The Kaizen approach within process innovation: findings from a multiple case study in Ibero-American countries - Suárez-Barraza, Manuel F.; Smith, Tricia (Total quality management & business excellence, 2014)
Processes and process innovation remains important in the management of today's organisations. In management and academic circles in Europe, Asia and the USA, the subject of processes and their innovation continue to be the basis of discussions regarding organisations' operations. The relevance of process innovation has gained weight as a result of various well-publicised failures by some major firms to operate new processes, leading to clients receiving low-quality goods and services. However, regarding the Iberian countries, academic references are few and far between regarding process innovation and Kaizen. Thus, it seems that previous studies represented in the literature show Kaizen from the angle of implementation of process innovation methods, and so the aim of this paper is to understand how these methods of process innovation are applied in the context of Kaizen in organisations operating in Ibero-American countries. This research has reported the results of a multiple case study, showing and providing empirical evidence grounded in the application of process innovation and the impact this has on the management of the organisation. In our study, we found that the application of process innovation basically can begin to help Ibero-American companies to understand (wake-up or become aware of) the deeper meaning of the term 'process' (theme of understanding); also, to begin to inspire (theme of synchronisation) the sense of managing from the point of view of process innovation and the philosophy of Kaizen in continuous improvement.